Influence of Electronic Media on The Reading Culture of Students of Selected Secondary Schools in Owo Local Government Area, Ondo State - Aladeniyi, Fasa Rachael; Idowu, Tope Ayoade; Owokole, Temitope Samuel (POMLIF Journal of Library and Information Science, 2021)
This study investigates the influence of electronic media on the reading culture of students of four selected secondary school in Owo Local Government Area of Ondo State. Descriptive survey research was adopted for the study. The population of the study comprises of S.S.S.1- S.S.S. 3 students of the selected secondary schools. Questionnaire was used as the instrument for data collection. Three hundred and sixty (360) copies were distributed while three hundred and fifty-eight (358) copies were duly returned and found valid for the study. The data gathered from the respondents were analyzed using frequency count and simple percentage. The findings of the study revealed that majority of the respondents accessed most of the electronic media listed in the questionnaire. Television was found to be the most accessed electronic media by the respondents and also influenced their reading culture most. The negative and positive influences of electronic media were also revealed in the study. As shown in the analysis, majority of the respondents agreed that electronic media improve their spoken English and also enables them read anywhere without carrying a physical reading materials. However, most of the respondents also indicates that electronic media is time consuming also divert their attention from doing their assignment. Based on the findings, some recommendations were made; this includes giving proper orientation to students on how to use electronic media in such a way that it will not influence their reading influence their reading culture negatively. Parental control on the use of electronic medias should be upheld in various homes and reading campaign should be initiated in secondary schools such as book club, reading competition, spelling bee etc.